Pengaruh Sosial Media Marketing, Selebriti Endorse, Dan Citra Merek Terhadap Kinerja Pemasaran Umkm Di Cikarang - Winda Aprila Monikawati; Windi Windi; Adibah Yahya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research analyzes the influence of Social Media Marketing, Celebrity Endorsement, and Brand Image on the Marketing Performance of SMEs in Cikarang. The method used is quantitative with a Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach through the SmartPLS 3.0 application. The results of the study indicate that Social Media Marketing has a positive but not significant effect, while Celebrity Endorsement and Brand Image have a positive and significant effect on marketing performance. The implications of these findings highlight the importance of strengthening brand image and collaborating with celebrities as effective marketing strategies for SMEs.